2014
DOI: 10.1186/preaccept-1149759184129961
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and characteristics of avoidant/restrictive food intake disorder in a cohort of young patients in day treatment for eating disorders

Abstract: BackgroundAvoidant/Restrictive Food Intake Disorder (ARFID) is a “new” diagnosis in the recently published DSM-5, but there is very little literature on patients with ARFID. Our objectives were to determine the prevalence of ARFID in children and adolescents undergoing day treatment for an eating disorder, and to compare ARFID patients to other eating disorder patients in the same cohort.MethodsA retrospective chart review of 7-17 year olds admitted to a day program for younger patients with eating disorders b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
178
5
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(200 citation statements)
references
References 19 publications
14
178
5
3
Order By: Relevance
“…Concurrent anxiety disorders are the most prevalent; they occur in more than 70% of patients in some clinical samples. 15 Rates of concurrent generalized anxiety disorder in particular have been estimated to be 50% among patients who are being treated for ARFID. 16 Major depressive disorder is also common among patients with ARFID, although it appears to occur less commonly in association with this condition than with anorexia nervosa and bulimia nervosa.…”
Section: Discussion Of Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Concurrent anxiety disorders are the most prevalent; they occur in more than 70% of patients in some clinical samples. 15 Rates of concurrent generalized anxiety disorder in particular have been estimated to be 50% among patients who are being treated for ARFID. 16 Major depressive disorder is also common among patients with ARFID, although it appears to occur less commonly in association with this condition than with anorexia nervosa and bulimia nervosa.…”
Section: Discussion Of Managementmentioning
confidence: 99%
“…16 Major depressive disorder is also common among patients with ARFID, although it appears to occur less commonly in association with this condition than with anorexia nervosa and bulimia nervosa. 15 …”
Section: Discussion Of Managementmentioning
confidence: 99%
“…7 Further, ARFID was even more common (22.5%) among youth in a day treatment program for eating disorders. 8 By contrast, a retrospective review of 2,231 consecutive referrals (aged 8–18 years) to pediatric gastrointestinal clinics in the Boston area showed an ARFID prevalence of only 1.5%. 9 A recent latent class analysis of three pediatric surveillance studies (in which pediatricians and child psychiatrists were asked to report on any children < 12 years with a newly diagnosed restrictive type eating disorder) performed across Canada, the United Kingdom, and Australia suggested that one of two identified clusters representing between 25–34% of children with incident restrictive type eating disorders mapped onto symptoms consistent with ARFID.…”
Section: What Is Currently Known?mentioning
confidence: 95%
“…Psychiatric comorbidities, including anxiety disorders, 5,6 autism spectrum disorder, 8 and attention deficit hyperactivity disorder (ADHD) 8 are common among individuals with ARFID. A retrospective chart review of 34 pediatric patients with ARFID indicated that 50% also had generalized anxiety disorder.…”
Section: What Is Currently Known?mentioning
confidence: 99%
“…Avoidant/restrictive food-intake disorder (ARFID), introduced as a new disorder in the fifth edition of the Diagnostic and Statistical Manual of Mental Disorders (DSM-5),7 is characterized by an eating or feeding disturbance resulting in significant weight loss or failure to achieve expected weight, nutritional deficiencies, dependence on enteral feeding or nutritional supplements, or interference with psychosocial functioning. Prevalence estimates range from 5%8 to 22.5%,9 depending on the treatment setting.…”
Section: Introductionmentioning
confidence: 99%